2019
DOI: 10.1111/1750-3841.14666
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of Extracts of 12 Melon (Cucumis melo) Peel Powders Prepared from Commercial Melons

Abstract: Melons are a diverse group of fresh, dessert fruits that includes orange flesh cantaloupe, green flesh honeydew, and mixed hybrid melons. As part of an effort to discover potential health benefits of fruit and vegetable peels that are considered to be byproducts of food processing, we determined the total phenolic content and antioxidative activities of methanolic extracts of the powdered peels of the following commercial melon (Cucumis melo) varieties sold at retail markets in California that were imported fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
2
28
0
2
Order By: Relevance
“…Table 6 shows that adding 5 or 10% Galia melon peels to wheat flour did not affect the acrylamide levels of the baked flatbreads. In a previous study, we have reported that the melon peel used here contained phenolic compounds and flavonoids, and showed the highest antioxidative activity of 12 evaluated melon peel powders [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 shows that adding 5 or 10% Galia melon peels to wheat flour did not affect the acrylamide levels of the baked flatbreads. In a previous study, we have reported that the melon peel used here contained phenolic compounds and flavonoids, and showed the highest antioxidative activity of 12 evaluated melon peel powders [16].…”
Section: Discussionmentioning
confidence: 99%
“…As part of this effort, we have shown that (a) the dietary supplementation of potato peel powders reduced weight gain in mice on a high-fat diet [12]; (b) potato peel powders inhibited the growth of pathogenic trichomonads (protozoa) that cause sexually transmitted diseases in humans and cattle [13]; (c) apple, orange, and potato peel powders inhibited the outgrowth of pathogenic Bacillus cereus bacteria from spores in cooked rice [14]; and (d) a rice hull smoke extract reduced weight gain in mice on a high-fat diet [15]. We also recently determined the content of phenolic and flavonoid compounds and antioxidative activities of 12 melon peel powders [16].…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the total phenolics content may be due to cantaloupe cultivars and growing locations. The prominent phenolic compounds reported in melon have been isovanillic acid, coumaric acid-hexoside, hydroxyl-benzoic acid hexoside, chlorogenic acid, apigenin-7-α-glucoside, ferulic acid, and luteolin-7-O-glucoside [ 36 , 44 ]. The antidiabetic potential of cantaloupe was evaluated by determining their capacity to inhibit the α-amylase activity that is responsible for breakdown of polysaccharides to monosaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in tomato plants, GABA enhanced the level of gallic and coumaric acids under salinity conditions [ 80 ]. Our results show that variety F-39 had high GABA ( Figure 4 ) and total phenolics content ( Figure 8 A) in NC and IN; this may be due to accumulation of phenolic acids such as ferulic and p-coumaric acids, which are known as prominent phenolic compounds in cantaloupe [ 36 , 44 ]. Similarly, the TT-DV variety also had high levels of GABA and total phenolics content in NC, IN, and AZ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation